Indicadores de evasão e baixa procura nos cursos de licenciatura do IFFAr – Campus São Vicente do Sul: rearticulações na gestão - Fonseca, Greice Lopes Maia (2018)
This dissertation was developed based on research on the weaknesses and potentialities of teacher training policies developed at Federal Institutes, under the legal obligation to offer at least 20% of annual vacancies for teacher training courses, imposed by Law of Creation of the Federal Institutes, Law No. 11,892 of 2008. The objective was to analyze the factors that interfere in the low demand for vacancies and in the avoidance of undergraduate courses at IFFAR - São Vicente do Sul Campus, in order to implement the expansion policy the Federal Network and Professional and Technological Education in Brazil and the strengthening of teacher training. The investigation is characterized as a case study developed from a historical-critical epistemological perspective, supported by a quantity-qualitative approach and based on a documentary analysis. The constructed data were analyzed from the methodological perspective of the content analysis of Bardin (2011). From this analysis it was possible to perceive that the situation of undergraduate courses in the locus of the research is very delicate, with evasion rates above 50% and annual efficiency index equal to 0% for the Chemistry course. In this scenario of apparent failure of the teacher education policy was a highly collaborative academic environment, which recognizes the existence of the problem in which undergraduate courses are immersed, but which still lacks a greater involvement of all actors in this scenario through institutional actions that encompass the well-intentioned actions that are taken by the course coordinators alone. In this sense, the final product of this research is precisely the elaboration of the Actions Rearticulation Plan to improve the efficiency indices of the São Vicente do Sul undergraduate degree courses, named PRA-Degrees, which translates as a set of integrated and cooperative actions that can help the management of undergraduate courses to change the scenario of high dropout and retention rates and low demand and graduation rates.